2016
DOI: 10.18632/oncotarget.12959
|View full text |Cite
|
Sign up to set email alerts
|

Different imaging techniques for the detection of pelvic lymph nodes metastasis from gynecological malignancies: a systematic review and meta-analysis

Abstract: ObjectiveThis study aimed to evaluate the diagnostic performance of different imaging techniques and the corresponding diagnostic criteria for preoperative detection of pelvic lymph node metastasis from gynecological carcinomas.MethodsSix databases were systematically searched for retrieving eligible studies. Study inclusion, data extraction and risk of bias assessment were performed by 2 reviewers independently. STATA 14.0 was used to perform the meta-analysis. Results: Eighty eligible studies were collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 90 publications
0
27
0
5
Order By: Relevance
“…Klerkx et al [ 25 ] have concluded that best sensitivity and specificity rates are acquired when short axis diameter of pelvic LN on the MR image is >8 mm, resulting in a sensitivity of 42.9% and specificity 96.6%. In one meta-analysis [ 26 ] , the authors recommended LN diameter ≥8 mm as the best cut-off value when short axis diameter was adopted as a positive criterion in MRI examination. According to the above research, we classified the patients into 2 groups: enlarged LN short diameter <0.8 cm, and enlarged short diameter ≥0.8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Klerkx et al [ 25 ] have concluded that best sensitivity and specificity rates are acquired when short axis diameter of pelvic LN on the MR image is >8 mm, resulting in a sensitivity of 42.9% and specificity 96.6%. In one meta-analysis [ 26 ] , the authors recommended LN diameter ≥8 mm as the best cut-off value when short axis diameter was adopted as a positive criterion in MRI examination. According to the above research, we classified the patients into 2 groups: enlarged LN short diameter <0.8 cm, and enlarged short diameter ≥0.8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Nierenhilus mit einbezogen werden. Die Diffusionswichtung ist bei der Sensitivität des Nachweises von Lymphknotenmetastasen der konventionellen MRT überlegen (p = 0,0006) bei vergleichbarer Spezifität (p = 1,00) [26]. Bei der Befundung der DWI sollte immer eine T2w oder T1w Sequenz mitbetrachtet werden, da auch normale Lymphknoten aufgrund ihre hohen Zelldichte eine relative Diffusionsrestriktion aufweisen und damit ebenfalls ein hohes Signal bei hohem b-Wert mit korrespondierender ADC-Absenkung zeigen [27].…”
Section: Ovarialtumorunclassified
“…Při zhodno cení LN pomocí zobrazovacích metod kolísá senzitivita (záchyt pozitivních LN) detekce postižených LN podle růz ných studií mezi 60-88 % se specificitou (počet falešně pozitivně hodnocených LN) dosahující až 97 % [5,15]. Recentní metaanalýza zjistila při hodnocení stavu LN nejvyšší specificitu pro ultrazvu kové vyšetření (99 %) ve srovnání s PET CT (97 %), MRI (95 %) a CT (93 %) [19]. Infiltrované LN jsou často < 5-10 mm, což je velká limitace pro MRI i PETCT, proto je senzitivita těchto vyšetření rela tivně malá a zvyšuje se až u pokročilých onemocnění [14,15].…”
Section: Introductionunclassified